A catalog of galaxies in the direction of the Perseus cluster - Wittmann, Carolin; Lisker, Thorsten; Grebel, Eva K. (The astrophysical journal. Supplement series, 2019)
We present a catalog of 5437 morphologically classified sources in the direction of the Perseus galaxy cluster core, among them 496 early-type low-mass galaxy candidates. The catalog is primarily based on V-band imaging data acquired with the William Herschel Telescope, which we used to conduct automated source detection and derive photometry. We additionally reduced archival Subaru multiband imaging data in order to measure aperture colors and perform a morphological classification, benefiting from 0.″5 seeing conditions in the r-band data. Based on morphological and color properties, we extracted a sample of early-type low-mass galaxy candidates with absolute V-band magnitudes in the range of −10 to −20 mag. In the color-magnitude diagram, the galaxies are located where the red sequence for early-type cluster galaxies is expected, and they lie on the literature relation between absolute magnitude and Sérsic index. We classified the early-type dwarf candidates into nucleated and nonnucleated galaxies. For the faint candidates, we found a trend of increasing nucleation fraction toward brighter luminosity or higher surface brightness, similar to what is observed in other nearby galaxy clusters. We morphologically classified the remaining sources as likely background elliptical galaxies, late-type galaxies, edge-on disk galaxies, and likely merging systems and discussed the expected contamination fraction through non-early-type cluster galaxies in the magnitude-size surface brightness parameter space. Our catalog reaches its 50% completeness limit at an absolute V-band luminosity of −12 mag and a V-band surface brightness of 26 mag arcsec−2. This makes it the largest and deepest catalog with coherent coverage compared to previous imaging studies of the Perseus cluster.
Gesehen am 12.02.2020